2020
DOI: 10.1007/s00268-020-05850-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ageing on Hepatic Malignancy Resection: Is Age Really a Risk Factor for Mortality?

Abstract: Background With an ageing population, it is paramount for surgeons to comprehend the implications of age on surgical outcomes. This study aims to identify the effects of age on perioperative outcomes post‐hepatectomy. Methods Between 2001 and 2017, 357 hepatectomies were performed in our centre for malignancy. Data recorded include demographic, histopathology and perioperative outcomes. Patients were divided into three age groups (Group 1 < 65 years, Group 2 65–74 years, Group 3 ≥ 75 years). Results With incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Additionally, we also revealed that aged ≥ 60 years, Child-Pugh grade B, tumor diameter ≥ 5 cm, and open hepatectomy were identified as risk factors for posthepatectomy complications, infectious and major complications in HCC and HBV-HCC patients, which is consistent with previous research findings [32][33][34][35][36]. This is because elderly patients may present with multiple comorbidities and experience gradual decline in organ function, resulting in compromised compensatory capacity of the liver and impaired regeneration ability of hepatocytes after radical resection [32]. Research has demonstrated that patients classified as Child-Pugh grade B (7 to 9 points) exhibit higher rates of postoperative complications and perioperative mortality compared to those Child-Pugh grade A (5 to 6 points) [33].…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, we also revealed that aged ≥ 60 years, Child-Pugh grade B, tumor diameter ≥ 5 cm, and open hepatectomy were identified as risk factors for posthepatectomy complications, infectious and major complications in HCC and HBV-HCC patients, which is consistent with previous research findings [32][33][34][35][36]. This is because elderly patients may present with multiple comorbidities and experience gradual decline in organ function, resulting in compromised compensatory capacity of the liver and impaired regeneration ability of hepatocytes after radical resection [32]. Research has demonstrated that patients classified as Child-Pugh grade B (7 to 9 points) exhibit higher rates of postoperative complications and perioperative mortality compared to those Child-Pugh grade A (5 to 6 points) [33].…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have shown that age is a relevant factor for complications in liver surgery (Trundle et al 2019 ; Laporte and Kalil 2013 ). With increasing age, the complication rate of liver surgery has gradually increased (Liu et al 2021 ). A study of 663 patients who underwent hepatectomy showed that the 90-day mortality rates were 11.0%, 13.0%, and 17% for patients aged > 70, 75, and 80 years, respectively, and that the complication rates were 53%, 57%, and 66%, respectively (Shutt et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we also revealed that aged ≥ 60 years, Child-Pugh grade B, tumor diameter ≥ 5 cm, and open hepatectomy were identi ed as risk factors for post-hepatectomy complications, infectious and major complications in HCC and HBV-HCC patients, which is consistent with previous research ndings. This is because elderly patients may present with multiple comorbidities and experience gradual decline in organ function, resulting in compromised compensatory capacity of the liver and impaired regeneration ability of hepatocytes after radical resection [33]. Research has demonstrated that patients classi ed as Child-Pugh grade B (7 to 9 points) exhibit higher rates of postoperative complications and perioperative mortality compared to those Child-Pugh grade A (5 to 6 points) [34].…”
Section: Discussionmentioning
confidence: 99%